Fresh air fiend eaudiobook Travel writings. - Theroux, Paul (Recorded Books Inc., 2014)
Internationally acclaimed author Paul Theroux adds Fresh Air Fiend, named a New York Times Notable Book, to his highly praised travel writings. A collection of essays, this intimate and fascinating book explores five continents and many cultures, while delving deep into the mind of Theroux. From one adventure to the next, listeners will be captivated by what the Chicago Tribune calls "an irresistable storyteller." "Theroux demonstrates his power to carry readers into different worlds and make those worlds 'realer' thorugh his agile and incisive prose."-Booklist